(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the therapeutic effects of standard medical treatment combined with electroacupuncture in the management of language disorders in patients with post-acute ischemic stroke, assessed by clinical language disorder scales at the National Hospital of Acupuncture. Subjects and methods: This was a clinical interventional study with a pre- and post-treatment comparison, conducted on 41 patients aged 18 years and older who were definitively diagnosed with first-ever post-acute ischemic stroke accompanied by language disorders and treated at the National Hospital of Acupuncture between August 2023 and September 2024. Patients received standard modern medical therapy combined with continuous electroacupuncture for 30 days. Treatment outcomes were evaluated using the Goodglass and Kaplan (1984) clinical aphasia assessment scale. Results: After 30 days of treatment, the proportion of patients with severe language disorders decreased from 53.66% to 31.71%, while the proportion of patients with mild language disorders increased from 4.48% to 58.54%. The mean severity score of language impairment improved significantly from 2.12 ± 1.12 to 3.34 ± 1.15 (p < 0.01). Regarding the degree of improvement, 31.71% of patients improved by two severity levels (type A), 58.54% improved by one level (type B), and 9.67% showed no improvement (type C), with the difference being statistically significant (p < 0.01). All patients with early disease onset (24 hours to 1 month) and those aged 18-49 years demonstrated improvement in aphasia severity. Conclusion: Electroacupuncture combined with standard medical therapy is effective in improving language disorders in patients with post-acute ischemic stroke.